Effects of fish oil on methotrexate-induced reproductive damage in rats - Ipek, Volkan; Kaya, Kursat; Cebi, Cigdem; Gurel, Ali; Ayozger, Leyla Elif Ozgu (Wiley, 2022)
Methotrexate (MTX) is a folic acid antagonist that is commonly used in paediatric and adult oncology to treat a variety of malignancies. Internal organs, including the testis, are severely cytotoxic and genotoxic to MTX. Omega-3, as an antioxidant, has been shown to protect rat testis tissue from injury. The effect of fish oil (FO) on MTX-induced reproductive damage in rats was investigated in this work. The 28 animals were divided into four groups for this purpose (control, FO, MTX, and MTX-FO). On the third day, the MTX group received a single intraperitoneal injection of 20 mg/kg MTX. Furthermore, in the FO and MTX-FO groups, FO was delivered through gavage once daily for 14 days. All animals euthanized under general anaesthesia on the 15th day. TBARS, catalase, glutathione peroxidase, glutathione (GSH), superoxide dismutase levels were measured biochemically. The Cosentino grading system was utilized for histology. Germ cell thickness and caspase-3 activity were also evaluated. In addition, sperm motility rate, epididymal sperm count, aberrant sperm rate, and sperm vitality were measured to assess sperm quality. Some TBARS levels have increased, but GSH levels decreased significantly in the MTX group. FO reduced TBARS levels while considerably increasing GSH levels. All sperm quality measures were significantly lowered in the MTX group, while FO had a recovery effect. There were no notable variations in histopathology across groups except for germ cell thickness, which reduced considerably in the MTX group and recovered with FO treatment. As a result, FO has been shown to reduce testicular toxicity following MTX treatment in rats.
Keywords: apoptosis; fish oil; histopathology; methotrexate; oxidative stress